Trends in computed tomography scan uses in Taiwan from 2000 to 2013. Issue 12 (December 2019) - Hsueh, Yung-Wei; Lin, You-Cheng; Lin, Ching-Heng; Chen, Hung-Chieh; Huang, Zheng-Yi; Chai, Jyh-Wen; Chen, Clayton Chi-Chang
Abstract : Background: The trends in computed tomography (CT) scan uses in Taiwan were examined in different age and sex groups and compared between catastrophic illness and noncatastrophic illness groups. Methods: This retrospective cohort study used data from the National Health Insurance Research Database (NHIRD) in Taiwan to analyze CT scan uses from the beginning of 2000 to the end of 2013. The number, annual growth rate, and cumulative fold change ratio were estimated in different groups classified by sex, age, or disease category (catastrophic illness, noncatastrophic illness). Results: The number of CT scan uses per million people per year in Taiwan increased 2.5 times from 24 257 in 2000 to 60 351 in 2013, at the average annual growth rate of 7.4% ± 5.9%. The annual number of CT scan uses in different age groups and disease category groups was significantly higher in males than in females. However, the average annual growth rate and the cumulative fold change ratio were slightly higher in females than in males. The majority of CT scan uses were in middle age and young adult groups. The annual number of CT scan uses in the young adult, child/adolescent, and middle age groups increased 3.7-, 3.5-, and 2.7-fold from 2000 to 2013, but decreased 0.8-fold in the old-age group. The annual number of CT scan uses was highest in the noncatastrophic illness group, followed by the catastrophic illness cancer group and catastrophic illness others group. Conclusion: CT scan uses in Taiwan increased continuously from 2000 to 2013, even in the groups with higher radiation-related cancer risk. Therefore, clinicians, radiologists, and medical policy makers should weigh diagnostic benefit against sex-specific and age-specific risks in the future.